ON INDEPENDENCE NUMBER OF STRONG GENERALIZED CYCLES PRODUCT - Badalyan, S. H.; Markosyan, S. E. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
In the present paper the independence number of generalized cycles product is investigated. A method for constructing the maximal independent set in the product graph is presented. The method is particularly based on a specific combinatorial problem, which is also solved in the paper. The main result generalizes the similar fact known for odd cycles [6].